Word Reading Skills of Beginning Non-Readers: Effects of Training With a Visible Orthography - Poole, Heather (My University, 2009)
The experiments presented here investigated the effects of manipulating the visibility of spelling patterns in English print, without concurrent oral segmentation, on the word identification skills of beginning non-readers. Visibility of the orthographic patterns was manipulated by presenting material organized into rime families (blocked) or with rime families distributed throughout training (unblocked), as well as through highlighting common rimes in the same colour of print. Experiment 1 demonstrated that while a program emphasizing the orthographic patterns in the English writing system (without concurrent phonological segmentation) led to rapid improvements in beginning non-readers' on line word identification, the benefits of such training did not persist beyond the training context. Experiments 2A and 2B investigated whether the failure to transfer word reading skills beyond the blocked training context was mitigated by training programs that required increased focus on the letter patterns (2A) and the letter-sound relations (2B). These manipulations did not influence performance; children continued to demonstrate poor transfer beyond the training context. Experiment 3 focused on determining the mechanisms underlying the poor transfer following blocked training. To evaluate performance, this final experiment used a novel measure comprising word identification as well as onset and rime identification. Training materials were blocked either by rimes or onsets. The question of interest was whether training on material that blocks by orthographic units allows children to identify the blocked units during training without actively decoding their letter-sound relations, thus decreasing the probability of forming connections between the graphemes and phonemes comprising them. Results indicated that this is the case when children were trained on material blocked by rimes, but not that blocked by onsets.
Visible Orthography Training And Beginning Reading Skills
Keywords: spelling patterns, english, oral segmentation, non-readers, rime families, rimes